Novel corticotropin-releasing hormone receptor genes (CRHR1 and CRHR2) linkage to and association with polycystic ovary syndrome - Mutaz Amin; Nicholas Horst; Rongling Wu; Claudia Gragnoli (BMC, 2023)
Abstract Background Women with polycystic ovarian syndrome (PCOS) have increased hypothalamic-pituitary-adrenal (HPA) axis activation, pro-inflammatory mediators, and psychological distress in response to stressors. In women with PCOS, the corticotropin-releasing hormone (CRH) induces an exaggerated HPA response, possibly mediated by one of the CRH receptors (CRHR1 or CRHR2). Both CRHR1 and CRHR2 are implicated in insulin secretion, and variants in CRHR1 and CRHR2 genes may predispose to the mental-metabolic risk for PCOS. Methods We phenotyped 212 Italian families with type 2 diabetes (T2D) for PCOS following the Rotterdam diagnostic criteria. We analyzed within CRHR1 and CRHR2 genes, respectively, 36 and 18 microarray-variants for parametric linkage to and/or linkage disequilibrium (LD) with PCOS under the recessive with complete penetrance (R1) and dominant with complete penetrance (D1) models. Subsequentially, we ran a secondary analysis under the models dominant with incomplete penetrance (D2) and recessive with incomplete penetrance (R2). Results We detected 22 variants in CRHR1 and 1 variant in CRHR2 significantly (p < 0.05) linked to or in LD with PCOS across different inheritance models. Conclusions This is the first study to report CRHR1 and CRHR2 as novel risk genes in PCOS. In silico analysis predicted that the detected CRHR1 and CRHR2 risk variants promote negative chromatin activation of their related genes in the ovaries, potentially affecting the female cycle and ovulation. However, CRHR1- and CRHR2-risk variants might also lead to hypercortisolism and confer mental-metabolic pleiotropic effects. Functional studies are needed to confirm the pathogenicity of genes and related variants.